Peranan Koperasi dalam Perekonomian Indonesia - Nasution, Selviana; Hidayati, Sabilah; Nasution, Putri Rahmadani; Hasyim (Ikatan Da'i Indonesia, 2024)
This article discusses the central role of cooperatives in the context of the Indonesian economy. Cooperatives, which are defined as a form of cooperation in which members work together to achieve common goals, have two main forms in Indonesia, namely social cooperatives and economic cooperatives. The objectives of cooperatives, as regulated in Republic of Indonesia Law Number 25 of 1992, include the advancement of members and society, as well as contribution to national economic development in accordance with Pancasila and the 1945 Constitution. The function and role of cooperatives, especially in the economic sector, involves economic development members and society, improving the quality of human life, and actively participating in economic activities. The article highlights the strategic role of cooperatives as main actors in various economic sectors, providers of the largest employment opportunities, developers of local economic activities, creators of new markets, sources of innovation, and contributors in maintaining a balanced balance of payments through export activities. By referring to Article 33 of the 1945 Constitution, cooperatives are considered to be the main pillar of the Indonesian economy, with the basis of economic democracy which emphasizes collective production for the common good. As an economic organization with a social dimension, cooperatives are directed to always prioritize serving the needs of members and the community rather than solely pursuing profits. Further efforts are needed to educate the public, improve cooperative governance, and provide policy support that supports the growth and development of cooperatives in Indonesia. In this way, it is hoped that cooperatives can continue to play a major role in building a sustainable and inclusive Indonesian economy.